Effect of paddy-straw based Total Mixed Ration (TMR) on milk yield, milk composition and rumen parameters in lactating Red Chittagong cows (Bangladesh Journal of Livestock Research, 2020)
This study was carried out for a period of 70 days to investigate the comparative advantages of feeding total mixed ration (TMR) over conventional feeding in Red Chittagong cows (RCC). 15 RCC milking cows were divided into 3 treatment groups in a Completely Randomized Design (CRD). Existing feeding was denoted as control group (T0). TMR made with 60% roughage and 40% concentrate in the forms of block (T1) and mash (T2) were provided to other treatment groups. DM and CP intake was significantly (p